Zoonozic Influenza Viruses and Their Risks for Humans - Zadorozhna, V.I.; Shahinіan, V.R.; Задорожна, В.І.; Шагінян, В.Р. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Based on a review of available literary sources and official reports, the world situation with zoonotic influenza was analyzed, and the risks related to the pandemic potential of zoonotic influenza viruses were considered. It is shown that against the background of the genetic diversity of avian and mammalian influenza viruses and their ability to reassort genes, there is a constant risk of the formation of pandemic virus variants for humans. Moreover, such an example already exists, namely the A(H1N1)pdm09 virus, which turned out to be a quaternary reassortant of swine, bird, and human influenza viruses with rapid adaptation to the human population. After the appearance of zoonotic avian influenza viruses AIV A(H5N1) in 1997, new zoonotic AIVs were discovered in the world: A(H9N2) (1998), A(H7N7) (2003), A(H7N3), A(H10N7) (2004), A( H7N9), A(H10N8) (2013), A(H5N6) (2014), A(H7N4) (2018), A(H10N3), A(H5N8) (2021), and A(H3N8) (2022). The last 3 viruses were identified during the COVID-19 pandemic. Zoonotic AIVs of different subtypes differ in their lethality in humans (for example, A(H5N1) has a 52% lethality, while A(H9N2) has a 2.2% lethality). They can also differ in their adaptation potential to the organism of mammals, particularly humans, even within the same subtype. During 2018 – 08/18/2023, 170 cases of influenza in humans caused by AIVs were registered in the world, among which A(H5N1) (10.6%) and A(H5N6) (39.4%) prevailed. Since 2021, their sharp growth has been observed (3 times compared to 2020 and 5.7 times compared to 2019). During the 2017/2018 – 2022/2023 seasons, 49 cases of swine flu caused by A(H1N1)v, A(H1N2)v, and A(H3N2)v viruses were reported in the world. Among them, A(H1N2)v prevailed (53.1%). The current trend of increasing avian influenza outbreaks among birds, mammals, and human cases with the expansion of geographic areas and the involvement of new species and categories of animals may be related to climate change, increased agricultural land, and poultry production. The increased effectiveness of epidemiological surveillance for severe respiratory syndrome, which occurred against the background of the COVID-19 pandemic, also contributed to the detection of new cases of zoonotic influenza in humans and the identification of new zoonotic influenza viruses. This requires constant monitoring of the circulation of both zoonotic influenza viruses and animal influenza viruses in general, as well as the selection of zoonotic influenza viruses – candidates for the production of vaccines in case of a worsening of the epidemic situation.